Formalin fixation for optimal concordance of programmed death‐ligand 1 immunostaining between cytologic and histologic specimens from patients with non–small cell lung cancer. Issue 4 (27th October 2020) - Koomen, Bregje M.; van der Starre‐Gaal, Jose; Vonk, Judith M.; von der Thüsen, Jan H.; van der Meij, Jacqueline J. C.; Monkhorst, Kim; Willems, Stefan M.; Timens, Wim; 't Hart, Nils A.
Abstract : Background: Immunohistochemical staining of programmed death‐ligand 1 (PD‐L1) is used to determine which patients with non–small cell lung cancer (NSCLC) may benefit most from immunotherapy. Therapeutic management of many patients with NSCLC is based on cytology instead of histology. In this study, concordance of PD‐L1 immunostaining between cytology cell blocks and their histologic counterparts was analyzed. Furthermore, the effect of various fixatives and fixation times on PD‐L1 immunoreactivity was studied. Methods: Paired histologic and cytologic samples from 67 patients with NSCLC were collected by performing fine‐needle aspiration on pneumonectomy/lobectomy specimens. Formalin‐fixed, agar‐based or CytoLyt/PreservCyt‐fixed Cellient cell blocks were prepared. Sections from cell blocks and tissue blocks were stained with SP263 (standardized assay) and 22C3 (laboratory‐developed test) antibodies. PD‐L1 scores were compared between histology and cytology. In addition, immunostaining was compared between PD‐L1–expressing human cell lines fixed in various fixatives at increasing increments in fixation duration. Results: Agar cell blocks and tissue blocks showed substantial agreement (κ = 0.70 and κ = 0.67, respectively), whereas fair‐to‐moderate agreement was found between Cellient cell blocks and histology (κ = 0.28 and κ = 0.49, respectively). Cell lines fixed in various alcohol‐based fixatives showed less PD‐L1 immunoreactivity compared with those fixed in formalin. In contrast to SP263, additional formalin fixation after alcohol fixation resulted in preserved staining intensity using the 22C3 laboratory‐developed test and the 22C3 pharmDx assay. Conclusions: Performing PD‐L1 staining on cytologic specimens fixed in alcohol‐based fixatives could result in false‐negative immunostaining results, whereas fixation in formalin leads to higher and more histology‐concordant PD‐L1 immunostaining. The deleterious effect of alcohol fixation could be reversed to some degree by postfixation in formalin. Abstract : Fixation of cytologic specimens in alcohol‐based fixatives results in negative effects on programmed death‐ligand 1 (PD‐L1) immunostaining when using PD‐L1 immunohistochemistry protocols validated on formalin‐fixed, paraffin‐embedded material. The use of formalin results in more histology‐concordant PD‐L1 immunostaining, and the deleterious effect of alcohol fixation potentially may be reversed to some degree by postfixation in formalin.